QUANTIFICATION AND QUALITY CONTROL OF TRIPLE-DRUG COMBINATION EMPLOYED FOR GASTRIC ULCER USING STABILITY-INDICATING SELECTIVE RP-HPLC TECHNIQUE - PAVANI, YADLA; ARAVIND, S.; ANNAM, CHARITHA; SUBBA RAO, MANNAM (International Journal of Applied Pharmaceutics, 2024)
Objective: A seven-day regimen consisting of vonoprazan (VNP), amoxicillin (AXC) and clarithromycin (CRC), administered twice daily, has been permitted and reimbursed by health coverage as initial therapy. No technique has been implemented yet to determine the quantities of VNP, AXC, and CRC combination. This work effectively aimed at estimating these medications (VNP, AXC, and CRC) at the same time by developing an HPLC technique that saves money and time. Methods: The VNP, AXC, and CRC were separated in a “Waters” column (C18 nature; 250 mm sized length; 4.6 mm sized internal diameter; 5 µm sized particle; 25 °C temperature). Phosphoric acid (0.1% in water; pH 4.2) and absolute methanol (50:50, v/v) comprise the mobile phase. The drug product, Voqueznatripak, was subjected to hydrolysis, oxidation, photolysis, and thermal stressors with the intent to cause enforced degradation. The suggested "HPLC conditions" were verified in compliance with ICH guidance. Results: The measurements had a linear range of 10–20 µg/ml for VNP and 250–750 µg/ml for AXC and CRC. The AXC, CRC, and VNP had LOQ’s 5.302 µg/ml, 5.487 µg/ml and 0.523 µg/ml, respectively. Precision measurements were<0.2% RSD and accuracy ranges were 99.40% to 101.46%. The newly devised “HPLC conditions” specificity attribute and stability-indicating quality were also validated by forced degradation tests. Conclusion: The newly devised “HPLC conditions” for analysing AXC, CRC, and VNP in formulation dosage form and stability samples might be adapted by quality control laboratories. The devised “HPLC conditions” is qualified and consistent to reveal and detect any probable change in the drug product assessments throughout stability experiments.